2017
DOI: 10.3961/jpmph.17.152
|View full text |Cite
|
Sign up to set email alerts
|

Risk Reduction of Breast Cancer by Childbirth, Breastfeeding, and Their Interaction in Korean Women: Heterogeneous Effects Across Menopausal Status, Hormone Receptor Status, and Pathological Subtypes

Abstract: ObjectivesThe purpose of this study was to examine the associations of childbirth, breastfeeding, and their interaction with breast cancer (BC) risk reduction, and to evaluate the heterogeneity in the BC risk reduction effects of these factors by menopause, hormone receptor (HR) status, and pathological subtype.MethodsBC patients aged 40+ from the Korean Breast Cancer Registry in 2004-2012 and controls from the Health Examinee cohort participants were included in this study after 1:1 matching (12 889 pairs) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…We found its significantly increased concentration in the plasma of BC patients with high Ki-67, which is consistent with the data that miR-21 promotes BC proliferation ( Qiu et al, 2018 ; Wang et al, 2019 ). Early menarche and reduced breastfeeding are considered as risk factors for BC ( Jeong et al, 2017 ; Khalis et al, 2018 ). We found associations of both factors with elevation of miR-21-5p in plasma of Kazakh women.…”
Section: Discussionmentioning
confidence: 99%
“…We found its significantly increased concentration in the plasma of BC patients with high Ki-67, which is consistent with the data that miR-21 promotes BC proliferation ( Qiu et al, 2018 ; Wang et al, 2019 ). Early menarche and reduced breastfeeding are considered as risk factors for BC ( Jeong et al, 2017 ; Khalis et al, 2018 ). We found associations of both factors with elevation of miR-21-5p in plasma of Kazakh women.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of lactation increases with increasing duration of lactation 44. The result of a case– control study showed that the combination of two protective factors (two or more childbirth and lactation for more than 13 months) could reduce the risk of developing breast cancer by up to 50% 88. Furthermore, breastfeeding may be associated with improvements in prognosis and a decreased rate of recurrence (HR, 0.70; 95% CI, 0.53–0.93) and an increased rate of survival among breast cancer patients, although this effect is different in different ER states 89.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Breastfeeding is a protective factor against breast cancer, the longer the breastfeeding, the greater the protective effect [ 27 , 28 ]. At the same time, the association of two protective factors (two or more childbirths and lactation for more than 13 months) could reduce the risk of developing breast cancer by up to 60% [ 29 , 30 ].…”
Section: Breast Cancer–incidence and Risk Factorsmentioning
confidence: 99%